Penyebaran Sifilis di Batavia 1905 – 1942: Perspektif Biokekuasaan dalam Sejarah Kesehatan Kolonial - Zahra Berliani Pawelling Gesang; Agus Setiawan; Bondan Kanumoyoso (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to examine the spread of syphilis across various social group and the government’s efforts to solve it. The focus is on ho syphilis could spread within society, leading to social problems, and how the local government attempted to contain it. To approach this issue, Michael Foucault’s theory of biopower is employed. Data were collected through a literature review and colonial archives published between 1905 and 1942, such as the Geneeskundig Tijdschrift voor Nederlandsch-Indië (Medical Journal of the Dutch East Indies) which accesed online, as well as secondary sources including books and scientific journal article. The data were than analyzed using the historical method, including heuristics (source collection), criticism (verification), interpretation (analysis), and historiography (historical writing). The result of this study conclude that syphilis, caused by the bacterium Treponema pallidum, spread in Batavian society due to the widespread and uncontrolled practice of prostitution. The disease could affect anyone regardless of care or social class, including Indigineous people. Chinese, an Europeans. It was more commonly experienced by women; therefore, it is not surprising that syphilis was often associated with women’s isease. The government had issued regulations to reduce the high incidence of syphilis in Batavia, such as montring sex workers and establishing night clinics. However, these efforts did not produce the desired results.